2019
DOI: 10.1016/j.heliyon.2019.e01427
|View full text |Cite
|
Sign up to set email alerts
|

Comparative field performances between conventional combine and mid-size combine in wetland rice cultivation

Abstract: In paddy cultivation, harvesting is the most important operation, which needs suitable machinery. Thus, this study was carried out to compare field performances and energy and environmental effect between the conventional 5 m cutting width NEW HOLLAND CLAYSON 8080, 82 kW@2500 rpm combine harvester running on a total net area of 42.78 ha of plots for two rice (Oryza sativa L.) cultivation seasons and the new mid-size 2.7 m cutting width WORLD STAR WS7.0, 76 kW@2600 rpm combine harvester running on a total net a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…KDC with mean EFC of 0.28 ha/hr contributed to 34.05% higher mean FC than WS. In paddy harvesting with mean EFC of 0.53 ha/hr, the WS consumed 18.46 l/ha (Elsoragaby et al, 2019). The results stated that the grain corn harvesting which consumed 12.57 l/ha of diesel had 31.91% lower fuel consumption than paddy harvesting per hectare with the same model WS (Elsoragaby et al, 2019).…”
Section: Fuel Consumption Analysismentioning
confidence: 87%
See 4 more Smart Citations
“…KDC with mean EFC of 0.28 ha/hr contributed to 34.05% higher mean FC than WS. In paddy harvesting with mean EFC of 0.53 ha/hr, the WS consumed 18.46 l/ha (Elsoragaby et al, 2019). The results stated that the grain corn harvesting which consumed 12.57 l/ha of diesel had 31.91% lower fuel consumption than paddy harvesting per hectare with the same model WS (Elsoragaby et al, 2019).…”
Section: Fuel Consumption Analysismentioning
confidence: 87%
“…A recent study showed that WS had also been used in wetland paddy harvesting with mean FE of 72% (Elsoragaby et al, 2019). High EFC can have low FE for instance, KDC which had 12% higher EFC, had 8% lower in FE than WS due to underutilization of working width (Table 3).…”
Section: Effective Field Capacity and Field Efficiencymentioning
confidence: 99%
See 3 more Smart Citations